PENDAMPINGAN PENGOLAHAN KEDELAI MENJADI SUSU KEDELAI - Lail, Jamalul (AJIE (Asian Journal of Innovation and Entrepreneurship), 2015)
Soy bean as a harvest of dusun Sentono should be use as maximized as can. It will increase profit if people could precess soybeans, for example by making soy milk. Based on that, the authors conducted a community service activities that teach teens and mother how to made soy milk.